PCSK9 and LRP5 in macrophage lipid internalization and inflammation. Issue 9 (29th September 2020) - Badimon, Lina; Luquero, Aureli; Crespo, Javier; Peña, Esther; Borrell-Pages, Maria
Abstract: Aims: Atherosclerosis, the leading cause of cardiovascular diseases, is driven by high blood cholesterol levels and chronic inflammation. Low-density lipoprotein receptors (LDLR) play a critical role in regulating blood cholesterol levels by binding to and clearing LDLs from the circulation. The disruption of the interaction between proprotein convertase subtilisin/kexin 9 (PCSK9) and LDLR reduces blood cholesterol levels. It is not well known whether other members of the LDLR superfamily may be targets of PCSK9. The aim of this work was to determine if LDLR-related protein 5 (LRP5) is a PCSK9 target and to study the role of PCSK9 and LRP5 in foam cell formation and lipid accumulation. Methods and results: Primary cultures of human inflammatory cells (monocytes and macrophages) were silenced for LRP5 or PCSK9 and challenged with LDLs. We first show that LRP5 is needed for macrophage lipid uptake since LRP5-silenced macrophages show less intracellular CE accumulation. In macrophages, internalization of LRP5-bound LDL is already highly evident after 5 h of LDL incubation and lasts up to 24 h; however, in the absence of both LRP5 and PCSK9, there is a strong reduction of CE accumulation indicating a role for both proteins in lipid uptake. Immunoprecipitation experiments show that LRP5 forms a complex with PCSK9 in lipid-loaded macrophages. Finally, PCSK9 participates in TLR4/NFkB signalling; a decreased TLR4 protein expression levels and a decreased nuclear translocation of NFκB were detected in PCSK9 silenced cells after lipid loading, indicating a downregulation of the TLR4/NFκB pathway. Conclusion: Our results show that both LRP5 and PCSK9 participate in lipid uptake in macrophages. In the absence of LRP5, there is a reduced release of PCSK9 indicating that LRP5 also participates in the mechanism of release of soluble PCSK9. Furthermore, PCSK9 up-regulates TLR4/NFκB favouring inflammation. Graphical Abstract: